The Nutcracker Suite Piano, Four-Hands: Op. 71a - TCHAIKOVSKY (G.Schirmer, Inc., 1918)
Di dalambuku ini terdapat lagu: Miniature Overture; March; Dance of the Candy Fairy; Russian Dance, "Trepak"; Arab Dance; Chinese Dance; Dance of the Reed-Flutes; Waltz of the Flowers.